2008
DOI: 10.1093/carcin/bgn241
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microtubule dynamic instability and turnover in MCF7 breast cancer cells by sulforaphane

Abstract: Sulforaphane (SFN), a prominent isothiocyanate present in cruciferous vegetables, is believed to be responsible along with other isothiocyanates for the cancer preventive activity of such vegetables. SFN arrests mitosis, possibly by affecting spindle microtubule function. A critical property of microtubules is their rapid and time-sensitive growth and shortening dynamics (dynamic instability), and suppression of dynamics by antimitotic anticancer drugs (e.g. taxanes and the vinca alkaloids) is central to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 46 publications
7
55
1
Order By: Relevance
“…botrytis var. italica, cultivars) with high levels in seeds and sprouts (Sivakumar et al, 2007;You et al, 2008), has been shown to have an inhibitory effect in cell system studies on tumor growth in prostate (Bhamre et al, 2009;Shankar et al, 2008), breast (Azarenko et al, 2008) and colon cancers (Ecker et al, 2008;Gamet-Payrastre et al, 2000;Plate and Gallaher, 2003).…”
Section: Glucosinolates and Healthmentioning
confidence: 99%
“…botrytis var. italica, cultivars) with high levels in seeds and sprouts (Sivakumar et al, 2007;You et al, 2008), has been shown to have an inhibitory effect in cell system studies on tumor growth in prostate (Bhamre et al, 2009;Shankar et al, 2008), breast (Azarenko et al, 2008) and colon cancers (Ecker et al, 2008;Gamet-Payrastre et al, 2000;Plate and Gallaher, 2003).…”
Section: Glucosinolates and Healthmentioning
confidence: 99%
“…29). Fixed cells were mounted on glass slides with antifade agent Prolong Gold-DAPI (Life Technologies, Inc.) to visualize DNA and examined by fluorescence microscopy (Nikon Eclipse E800, Â40 objective).…”
Section: Mitotic Arrestmentioning
confidence: 99%
“…Cells were seeded as described above for cell viability on poly-L-lysine-treated coverslips, incubated with drug 24 hours, fixed with 3.7% formaldehyde followed by cold methanol (29) and stained with mouse monoclonal a-tubulin antibody (1:1,000 DM1A) and FITC-conjugated goat anti-mouse antibody (1:1,000, Cappel MP Biochemicals). Centrosomes were stained with rabbit polyclonal anti-pericentrin antibody (1:500, AB4448; Abcam) and rhodamine-conjugated goat anti-rabbit antibody (1:500, Cappel).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…One major mechanism of acquired drug resistance is the overexpression of efflux pumps, i.e., the p-gp170/MDR (21,(27)(28)(29)(30)(31), and many clinically used drugs are good substrate of the drug efflux pump (21,27). To test the effect of MDR expression on the sensitivity of tumor cells to BFBTS, we used MCF7/adr and human epidermoid carcinoma cell line KBv200, where the overexpression of MDR1 is induced by exposure to low dose of vinblastine or daunorubincin (28)(29)(30)(31). The MCF7/adr and KBv200 as well as their parental lines (MCF7 and KB) were treated with different concentrations of BFBTS and paclitaxel, and the cell responses were continuously monitored in real-time for 48 hours after treatment.…”
Section: Inhibition Of Cancer Cell Proliferation and Induction Of Apomentioning
confidence: 99%